UPR Responsive Genes Manf and Xbp1 in Stroke - Lõhelaid, Helike; Anttila, Jenni E.; Liew, Hock-Kean; Tseng, Kuan-Yin; Teppo, Jaakko; Stratoulias, Vassilis; Airavaara, Mikko (Frontiers in Cellular Neuroscience, 2022)
Stroke is a devastating medical condition with no treatment to hasten recovery. Its abrupt nature results in cataclysmic changes in the affected tissues. Resident cells fail to cope with the cellular stress resulting in massive cell death, which cannot be endogenously repaired. A potential strategy to improve stroke outcomes is to boost endogenous pro-survival pathways. The unfolded protein response (UPR), an evolutionarily conserved stress response, provides a promising opportunity to ameliorate the survival of stressed cells. Recent work from us and others has pointed towards mesencephalic astrocyte-derived neurotrophic factor (MANF) being an UPR responsive gene with an active role in maintaining proteostasis. Its pro-survival effects have been demonstrated in several disease models, such as diabetes, neurodegeneration, and stroke. MANF has an ER-signal peptide and an ER-retention signal, it is secreted by ER calcium depletion, and exits the cells upon cell death. Although its functions still remain elusive, conducted experiments suggest that endogenous MANF in the ER lumen and exogenously administered MANF protein have different mechanisms of action. Here, we will revisit recent and older literature aiming to delineate the expression profile of MANF. We will focus on its neuroprotective roles in regulating neurogenesis and inflammation upon post-stroke administration. At the same time, we will investigate commonalities and differences to another UPR responsive gene, X-box binding protein 1 (XBP1), which has recently been associated with MANF’s function. This will be the first systematic comparison of these two UPR responsive genes aiming at revealing previously uncovered associations among them. Overall, understanding the mode of action of these UPR responsive genes could provide novel approaches to promote cell survival.